The Influence of Customer Value and Brand Image on Customer Satisfaction - Rustan Ali; Ulyana Muslimin; Arfandy Dinsar (Amsir Management Journal, 2020)
This research aims to reveal and analyze how much influence customer value and brand image to customer satisfaction PT Bussan Auto Finance Parepare. In this research, the authors used a sample with the Slovin formula to obtain a sample size of 383 customers. The data analysis technique used to process the questionnaire result data was multiple linear regression analysis. The results showed that all independent variables, namely customer value (0.441) and brand image (0.484), had a positive and significant effect on the dependent variable, in this case, customer satisfaction at PT Bussan Auto Finance Parepare, this is evidenced by the statistical results Fhitung of 353.562 with a significance value of 0.000. Therefore the significance value is smaller than 0.05. So this research is successful in proving the hypothesis which states that it is assumed that customer value and brand image have partially and simultaneously positive effects on customer satisfaction at PT Bussan Auto Finance Parepare.